A new species of the genus Rhipidia Meigen, 1818 (Diptera: Limoniidae) from Tajikistan - V.I. Devyatkov (Кавказский энтомологический бюллетень, 2023)
A new species Rhipidia (Rhipidia) mesasiatica sp. n. (Diptera: Limoniidae) is described and illustrated based on male and female imagoes from Tajikistan, Badakhshan Mountainous Autonomous Region. This species belongs to the Rhipidia species-group with numerous small spots on the wings, but differs from them in the combination of some main diagnostic features: male antenna with seven bipectinate flagellomeres; thorac pleuron brown with one indistinct dark brown longitudinal stripe; wings with a relatively short vein Sc, vein Sc1 ending less one-third of Rs length; rostral prolongation of ventral gonostylus relatively long, with tuft of 4–5 long setae-like rostral spines nearer to apex